PENENTUAN CADANGAN AWAL ISI MINYAK DENGAN MENGGUNAKAN SOFTWARE MATERIAL BALANCE PADA RESERVOIR TGB - Muhammad Dimas Adiguna; Babas Samudera Hafwandi; Lindia Heviyanti; Ardipratama Ilham Vembriatmaja (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2026)
Reservoir TGB is a sandstone reservoir that began production in December 2019 and, as of November 2024, has been developed by two producing wells with a cumulative oil production of approximately 374 MSTB. Along with the increasing production activities and the need for field development planning, an evaluation of hydrocarbon reserves is required to assess the reservoir’s future production potential. This study aims to determine the Original Oil in Place (OOIP), identify the reservoir drive mechanism, and estimate the Estimated Ultimate Recovery (EUR) and remaining reserves of Reservoir TGB using the material balance method. The material balance analysis was conducted using oil, gas, and water production data, reservoir pressure data, and fluid property (PVT) data. History matching was performed using MBAL software to achieve consistency between the reservoir model and actual production behavior. Furthermore, the reservoir drive mechanism was evaluated through energy plot analysis and reservoir performance assessment. Decline curve analysis was subsequently carried out using OFM software to estimate the productive life and ultimate recovery potential of the reservoir. The results indicate that the OOIP of Reservoir TGB is approximately 3,000 MSTB. The evaluation of the drive mechanism shows that the reservoir is dominated by a water drive system. Based on the decline curve analysis, the EUR is estimated at 613.7 MSTB, with remaining reserves of 239.08 MSTB and a recovery factor of approximately 20.46%. These results indicate that a significant portion of hydrocarbons remains unrecovered. Therefore, further field development through the addition of production wells is recommended to improve oil recovery and optimize the utilization of the remaining reserves in Reservoir TGB.